Development of an α-linolenic acid containing soft nanocarrier for oral delivery: in vitro and in vivo evaluation. Issue 81 (16th August 2016) - Singh, Mahendra; Kanoujia, Jovita; Singh, Pooja; Tripathi, Chandra B.; Arya, Malti; Parashar, Poonam; Sinha, Vivek R.; Saraf, Shubhini A.
Abstract : Use of α-linolenic acid as an oil phase for microemulsion preparation with synergistic effect of oil in lowering of lipid levels in combination with simvastatin. Abstract : The oral bioavailability of simvastatin (SIM) a 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA) inhibitor is about 5%. That may be due to low intestinal permeability and hepatic first pass metabolism (FPM). The objective of the present investigation was to increase the therapeutic efficacy of SIM via developing a soft nanocarrier i.e. a microemulsion to enhance the intestinal permeability in addition to bioavailability. α-Linolenic acid (ALA) was used in the oil phase with Kolliphor EL 40 as surfactant and Transcutol HP as cosurfactant. A microemulsion formulation was developed for the oral delivery of SIM and characterized for physicochemical parameters. The SIM-loaded microemulsion (MES) was investigated for pharmacodynamic and pharmacokinetic parameters to investigate its suitability as a potential drug delivery system for the treatment of Hyperlipidemia in albino Wistar rats. In pharmacodynamic studies, significant differences in parameters were found between the optimized and marketed formulations. Optimized MES showed significantly higher ( P < 0.05) C max (107.84 ± 8.95 ng ml −1 ) than marketed tablets (57.65 ± 4.48 ng ml −1 ). It was found that AUClast obtained from the optimized MES (409.6 ± 22.54 ng h ml −1 ) was significantly higher ( P < 0.01) than the marketed tablet (155.4 ± 12.78 ng h mL −1 ). The relative bioavailability ( F r ) of the optimized formulation was about 263.5% higher than that of the marketed tablets. Optimized MES exhibited no cytotoxicity. Cellular uptake studies confirmed payload delivery to a cellular site (J774.A1 cell line). The results prove that the prepared microemulsion formulation is an improved and effective oral delivery of SIM for the management of lipid levels.